(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2023)
Fruits and vegetables are commonly consumed foods that are rich sources of essential vitamins, fibres, antioxidants, and bioactive compounds. Most of these vegetables and fruits are eaten raw without much processing and can serve as vehicles for the transmission of parasites and microorganisms. This study aimed to determine the prevalence of helminths in commercially marketed fruits and vegetables in Lokoja metropolis, Kogi State, Nigeria. One-hundred and eight (108) fruits and vegetables were sampled from three (3) different markets within Lokoja and examined for parasite contamination using wet mount and microscopy. A total of 27 (25%) fruits and vegetables were positive for parasite contamination while 81 (75%) were negative. Of the 27 parasite-contaminated fruits and vegetables, cabbage (29.63%) was the most contaminated, followed by lettuce (22.22%), mango (18.52%), guava (14.81%), cucumber (11.11%), and apple (3.70%). Twelve (44.44%) of the contaminated fruits and vegetables were purchased from Natako market, 10 (37.04%) were purchased from Kpata market, and 5 (18.52) were purchased from Lokongoma market. Although the frequency of fruits and vegetables contaminated with parasites was significantly lower than the number without parasite contamination (p<0.05), there was no significant difference in the prevalence of parasites contaminating different vegetables and fruits (p>0.05). A total of 4 helminths were isolated as contaminants of fruits and vegetables in Lokoja metropolis. Of these, Strongyloides stercoralis (40.74%) was the most prevalent, followed by Ascaris lumbricoides (25.93%), Trichuris trichiura (18.52%), and Hookworm (14.81%). Hence, fruits and vegetables should be properly washed with clean water before consumption.